2016
DOI: 10.1097/ta.0000000000000902
|View full text |Cite
|
Sign up to set email alerts
|

Geographic distribution of trauma centers and injury-related mortality in the United States

Abstract: Background Regionalized trauma care improves outcomes; however access to care is not uniform across the US. The objective was to evaluate whether geographic distribution of trauma centers correlates with injury mortality across state trauma systems. Methods Level I/II trauma centers in the contiguous US were mapped. State-level age-adjusted injury fatality rates/100,000people were obtained and evaluated for spatial autocorrelation. Nearest neighbor ratios (NNR) were generated for each state. A NNR<1 indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(80 citation statements)
references
References 24 publications
1
76
2
1
Order By: Relevance
“…Only children presenting to Level I and Level II ACS‐verified trauma centers are included in the study; therefore, results may not be generalizable to patients presenting to other emergency settings . This may result in an underrepresentation of children with farm injuries who presented to their closest emergency department for medical attention, but did not require transfer to a trauma center . The NTDB is not nationally representative of all trauma centers; however, it currently includes over 95% of all US‐certified Level I and II trauma centers .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only children presenting to Level I and Level II ACS‐verified trauma centers are included in the study; therefore, results may not be generalizable to patients presenting to other emergency settings . This may result in an underrepresentation of children with farm injuries who presented to their closest emergency department for medical attention, but did not require transfer to a trauma center . The NTDB is not nationally representative of all trauma centers; however, it currently includes over 95% of all US‐certified Level I and II trauma centers .…”
Section: Discussionmentioning
confidence: 99%
“…7,26 This may result in an underrepresentation of children with farm injuries who presented to their closest emergency department for medical attention, but did not require transfer to a trauma center. 27 The NTDB is not nationally representative of all trauma centers; however, it currently includes over 95% of all US-certified Level I and II trauma centers. 23,26 Administrative data collected within the NTDB is subject to coding inaccuracies and misreport through physician documentation and trauma registrar collection of data.…”
Section: Limitationsmentioning
confidence: 99%
“…11 Motor vehicle collisions (MVC) have been shown to be particularly influenced by geographical factors, as several have shown that mortality from MVC is influenced by geographic region, population density, and vehicle miles traveled. 1215 Further, MVC events are dispersed throughout a trauma system and have a wide range of injury severity that mobilizes the full range of prehospital and trauma center resources.…”
Section: Introductionmentioning
confidence: 99%
“…The area based patterns may reflect the social ecology of these communities which also influences the choice and ability to undertake or maintain appropriate interventions and policies . Reflecting on the geographical contiguity of injury can influence where resources are targeted, highlight where variations in exposures exist with distinct socioeconomic characteristics and provide useful data for comparisons into the effectiveness of current prevention programs . By framing this evidence within a geographical context, we can start a conversation and raise awareness of local injury status in regional public health units and with other local stakeholders.…”
Section: Discussionmentioning
confidence: 99%